2003
DOI: 10.1046/j.1471-0528.2003.00015.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal short femur length in the second trimester and the outcome of pregnancy

Abstract: We reviewed 86 consecutive cases with fetal femur length (FL) below the 10th centile of our reference ranges at midtrimester ultrasonography. Three groups were identified based on perinatal outcome: normal infants (n ¼ 28), newborns with structural and/or chromosomal anomalies (n ¼ 40), small-for-gestational age (SGA) newborns (n ¼ 18). Fetuses with skeletal dysplasias (n ¼ 13) had significantly shorter FL. Aneuploidies were only found in fetuses with malformations other than skeletal dysplasias. The diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(82 citation statements)
references
References 9 publications
7
71
4
Order By: Relevance
“…while chromosomal disorders are more frequent (19%, 16/86) [26], therefore aneuploidy studies are always advisable. The interpretation of US finding in non-lethal types is even more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…while chromosomal disorders are more frequent (19%, 16/86) [26], therefore aneuploidy studies are always advisable. The interpretation of US finding in non-lethal types is even more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…(O'Brien et al, 1982) In one study, 18 of the 86 fetuses (21%) referred for FL below the 10th percentile had SGA. (Todros et al, 2004) The diagnosis of SGA in fetuses was confirmed about 9 weeks after the initial finding of short FL. In another study short FL was associated with low birth weight and SGA, but not with gestational hypertension.…”
Section: Femur Length and Intrauterine Growth Restrictionmentioning
confidence: 92%
“…(Papp et al,2006) Todros et al evaluated the outcome of pregnancy in 86 fetuses diagnosed with short FL in the second trimester ultrasonography scanning. (Todros et al, 2004) Twenty-eight of the fetuses (32.5%) were normal, 40 (46.5%) were structurally abnormal and 18 (21%) were small for gestational age. Of the 40 malformed fetuses, 16 (40%) were aneuploid.…”
Section: Femur Length and Aneuplodiesmentioning
confidence: 98%
See 2 more Smart Citations